Quantitative environmental assessment of explosive residues from the detonation of Insensitive High Explosive filled 155 mm artillery shell - Persico, Federica; Temple, Tracey; Ladyman, Melissa K.; Gilroy-Hirst, William; Guiterrez-Carazo, Encina; Coulon, Frederic (Wiley, 2022)
Insensitive High-Explosive (IHE) typically comprises up to five constituents including 2,4-dinitroanisole (DNAN), 3-nitro-1,2,4-triazol-5-one (NTO), and 1,3,5-trinitroperhydro-1,3,5-triazine (RDX), which are mixed in various ratios to achieve desired performance and increase insensitivity. Insensitive munitions, which are designed to detonate on command and not accidentally, are currently in use in military operations and training areas around the world. However, there is minimal literature available on the physiochemical behavior of these materials in the environment, therefore the actual consequence of residues being deposited post-detonation is still an unexplored area of research. Three 155 mm artillery shells filled with an IHE mixture of 53 % NTO, 32 % DNAN, and 15 % RDX were detonated in an inert sand arena to collect and quantify residues. Post detonation, approximately 0.02 % NTO, and 0.07 % DNAN were deposited in the environment which may rapidly accumulate dependent on the number of rounds fired. This is of concern due to the toxicity of DNAN and its degradation products, and the potential for increased acidity of soil and discoloration of watercourses from NTO contamination.
Keywords: 3-nitro-1,2,4-triazol-5-one (NTO); 2,4-dinitroanilisole (DNAN); 1,3,5-trinitroperhydro-1,3,5-triazine (RDX); Explosive residue; Multi-Increment sampling